An effective Coarse‐grained model for biological simulations: Recent refinements and validations. Issue 7 (6th December 2013) - Vicatos, Spyridon; Rychkova, Anna; Mukherjee, Shayantani; Warshel, Arieh
ABSTRACT Exploring the free energy landscape of proteins and modeling the corresponding functional aspects presents a major challenge for computer simulation approaches. This challenge is due to the complexity of the landscape and the enormous computer time needed for converging simulations. The use of various simplified coarse grained (CG) models offers an effective way of sampling the landscape, but most current models are not expected to give a reliable description of protein stability and functional aspects. The main problem is associated with insufficient focus on the electrostatic features of the model. In this respect, our recent CG model offers significant advantage as it has been refined while focusing on its electrostatic free energy. Here we review the current state of our model, describing recent refinements, extensions, and validation studies while focusing on demonstrating key applications. These include studies of protein stability, extending the model to include membranes, electrolytes and electrodes, as well as studies of voltage‐activated proteins, protein insertion through the translocon, the action of molecular motors, and even the coupling of the stalled ribosome and the translocon. The examples discussed here illustrate the general potential of our approach in overcoming major challenges in studies of structure function correlation in proteins and large macromolecular complexes. Proteins 2014; 82:1168–1185. © 2013 Wiley Periodicals, Inc.